Budaya Keselamatan Pasien Berdasarkan Indikator Agency for Healthcare Research and Quality di RSUD Dr. Soetomo - Thinni Nurul Rochmah; Maya Weka Santi; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (FORIKES, 2019)
In the National Standard for Accreditation of Hospitals (SNARS) 2018, patient safety is one of the standards of assessment. The purpose of this study was to assess the fair and open culture in the patient safety culture survey, with the aim of assessing the culture of reporting and learning in Dr. Soetomo Hospita, Surabaya. This research was an observational study with a total sample of 406 employees spread across 34 installations and 11 fields / sections, with the same proportion. Data was collected using Hospital Survey on Patient Safety Cuture issued by AHRQ (Agency for Healthcare Research and Quality), which consisted of 12 dimensions. The results showed that the majority of employees had assessed the 12 AHRQ dimensions well, but there were several dimensions that still received poor ratings such as openness of communication, bad = 25.4%, frequency of incident reporting, rarely = 27.8% and staffing, less 39.6%; it is necessary to develop a culture of not blaming if someone reports an incident, and changes in staffing to suit the workload. Keywords: Agency for Healthcare Research and Quality, patient safety, hospital ABSTRAK Dalam Standar Nasional Akreditasi Rumah Sakit (SNARS) 2018, keselamatan pasien merupakan salah satu standar penilaian. Tujuan penelitian ini adalah untuk menilai budaya adil dan terbuka dalam survei budaya keselamatan pasien, dengan tujuan menilai budaya pelaporan dan pembelajaran di RSUD Dr. Soetomo Surabaya. Penelitian ini merupakan studi observasional dengan total sampel 406 karyawan yang tersebar di 34 instalasi dan 11 bidang/bagian, dengan proporsi yang sama. Data dikumpulkan menggunakan Hospital Survey on Patient Safety Cuture yang dikeluarkan oleh AHRQ (Agency for Healthcare Research and Quality), yang terdiri atas 12 dimensi. Hasil penelitian menunjukkan bahwa sebagian besar karyawan telah menilai baik pada 12 dimensi AHRQ, namun terdapat beberapa dimensi yang masih mendapat penilaian buruk seperti keterbukaan komunikasi, buruk=25,4%, frekuensi pelaporan insiden, jarang=27,8% dan staffing, kurang=39,6%; maka perlu dikembangkan budaya tidak menyalahkan jika ada yang melaporkan insiden, dan perubahan susunan kepegawaian agar sesuai dengan beban kerja. Kata kunci: Agency for Healthcare Research and Quality, keselamatan pasien, rumah sakit